Advanced Self-Healing Asphalt Composites in the Pavement Performance Field: Mechanisms at the Nano Level and New Repairing Methodologies - Agzenai, Yahya; Pozuelo, Javier; Sanz, Javier; Perez, Ignacio; Baselga, Juan (Recent Patents on Nanotechnology, 2015)
In an effort to give a global view of this field of research, in this mini-review we highlight the most recent publications and patents focusing on modified asphalt pavements that contain certain reinforcing nanoparticles which impart desirable thermal, electrical and mechanical properties. In response to the increasing cost of asphalt binder and road maintenance, there is a need to look for alternative technologies and new asphalt composites, able to self-repair, for preserving and renewing the existing pavements. First, we will focus on the self-healing property of asphalt, the evidences that support that healing takes place immediately after the contact between the faces of a crack, and how the amount of healing can be measured in both the laboratory and the field. Next we review the hypothetical mechanisms of healing to understand the material behaviour and establish models to quantify the damage-healing process. Thereafter, we outline different technologies, nanotechnologies and methodologies used for self-healing paying particular attention to embedded micro-capsules, new nano-materials like carbon nanotubes and nano-fibres, ionomers, and microwave and induction heating processes.
Keywords: micro-capsules